2019
DOI: 10.12968/bjom.2019.27.5.312
|View full text |Cite
|
Sign up to set email alerts
|

Have interventions been effective at increasing the rates of breastfeeding in the UK?

Abstract: Background The World Health Organization recommends exclusive breastfeeding for the first 6 months of life; however, UK breastfeeding rates are some of the lowest worldwide. As such, various interventions have been trialled, aiming to increase breastfeeding rates. Aims To evaluate the effectiveness of interventions to increase breastfeeding rates in the UK and determine the features of successful interventions. Methods A literature search was performed, using four databases. The results were refined by applyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…A previous study found that combined interventions in the form of motivation, support and incentives could increase breastfeeding success. Interventions mainly take the form of efforts to overcome breastfeeding difficulties and provide appreciation for the efforts made by breastfeeding women 34,35 .…”
Section: Motivation or Rewards For Breastfeeding Womenmentioning
confidence: 99%
“…A previous study found that combined interventions in the form of motivation, support and incentives could increase breastfeeding success. Interventions mainly take the form of efforts to overcome breastfeeding difficulties and provide appreciation for the efforts made by breastfeeding women 34,35 .…”
Section: Motivation or Rewards For Breastfeeding Womenmentioning
confidence: 99%
“…Whilst efforts are being made to increase breastfeeding rates through campaigns such as the exclusive feeding initiatives introduced by the World Health Organisation (WHO, 2011), rates in the UK are still very low (Shortis, 2019). As such many young women within the UK are unlikely to have direct experience of breastfeeding, which in turn is likely to perpetuate low rates.…”
Section: Implications For Practice and Policymentioning
confidence: 99%
“…While many initiatives have attempted to improve breastfeeding rates in the UK (Shortis, 2019), decisions surrounding infant feeding tend to be made prior to pregnancy or in the first trimester (Sheehan et al 2013) with factors such as; physical problems, embarrassment, social pressure, a lack of accurate information and unsupportive partners of breastfeeding women having an influential role (Hauck et al 2010;Oakley et al 2014;Feenstra et al 2018). A literature review of breastfeeding discontinuation before 6 months identified that a lack of support (either from significant others close to the breastfeeding mother or from health professionals), poor physical or emotional health of the mother and an insufficient milk supply were the main reasons, other than maternal choice for early cessation of breastfeeding (Wray & Garside, 2018).…”
Section: Introductionmentioning
confidence: 99%